Altered microbial communities and nitrogen availability in temperate forest edges. (January 2018) - Remy, Elyn; Wuyts, Karen; Verheyen, Kris; Gundersen, Per; Boeckx, Pascal
Abstract: Due to forest fragmentation, forest edges have become dominant features in landscapes around the world. Forest edges are exposed to a different microclimate and to higher atmospheric nitrogen (N) deposition compared to the forest interior. It is still unclear how both factors affect N cycling at temperate forest edges. In this study, the microbial community structure was mapped using phospholipid fatty acids (PLFA) in forest edge (0–5 m) and interior (64 m) in two oak ( Quercus robur ) stands, two pine ( Pinus nigra ) stands and one spruce ( Picea sitchensis ) stand in northern Belgium and Denmark. Nitrogen mineralization, nitrification and immobilization rates were obtained via the in situ 15 N pool dilution technique in the forest edge and interior, and linked to the microbial community structure. Furthermore, we assessed 15 N recovery in simulated throughfall via the 15 N tracing method in edge and interior as a proxy for the long-term fate of mineral N. Microbial biomass was higher at the forest edges compared to the forest interiors and was associated to the higher gross mineralization rates. Gross nitrification rates were not increased at the edge, hereby preventing NO3 − leaching losses. Gross and net nitrification rates differed between the forest types, where the oak stands were characterized by higher nitrification rates than the pine and spruce stands. The oak stand retained 15 NO3 − in the mineral soil at the edge, while in the pine stand the polyphenol-rich litter layer retained more 15 NO3 − in the forest interior. Overall, our results indicated that the specific characteristics of the forest edge (atmospheric deposition, microclimate, pH of mineral soil and C/N ratio of the forest floor) increased microbial biomass and gross mineralization rates. Given the omnipresence of forest edges, more research should be conducted to validate our observations for other forest and soil types. Highlights: Forest edges differ from the interior in terms of N deposition and microclimate. Higher microbial biomass at the edge was linked to increased mineralization. Nitrification rates differed between the three forest types (oak > pine, spruce). Pine litter retained N in the interior, while the oak edge stored N in mineral soil.